Institutional Gaps in Agonistic and Communicative Planning Theories. Critical Implications of the ‘Systemic Turn’ in Deliberative Democracy Theory - Mäntysalo, Raine; Mattila, Hanna; Hirvola, Aino (Raumforschung und Raumordnung | Spatial Research and Planning, 2023)
The paper critically reviews communicative and agonistic planning theories from the viewpoint of a systemic turn in deliberative democracy theory. While the approach reveals complementarities between the theories, it also argues that each theory is vulnerable to criticism because of an ‘institutional gap’. The theories are found to complement each other in addressing planning conflicts at different dimensions. Communicative planning theory deals with conflicts between different stakeholders’ interests in planning processes. Agonistic planning theory, in turn, concentrates on conflicts from a more ontological dimension, related to the (implicit) conflict between hegemonic and marginalized discourses and related identity-forming processes of inclusion and exclusion in planning policies and governance. The institutional gap of communicative planning theory is argued to reside in its focus on situational deliberation that largely ignores the institutional dimension of rules and norms of democratic conduct. Agonistic pluralism, in turn, does engage with the dimension of democratic institutions, but in an overly critical manner, making it difficult for agonistic planning theory to address the dynamic interplay between institutional reconfiguration and policy stabilization in planning. This is argued to be the institutional gap of agonistic planning theory. The paper calls for further work in the field of planning theory to incorporate a systemic approach to deliberative democracy and thereby tap into the dialectics of institutional and situational dimensions of planning.
Keywords: Conflict; Consensus; Democratic institution; Hegemonic discourse; Situational deliberation